The Influence of Media Diversification Model and Entrepreneurship on Enterprise Financial Performance Under the Environment of Sustainable Development - Li, Xinying; Lou, Shuaifu; Zhu, Huiqin (Frontiers in Psychology, 2022)
Market competition is intensifying. The necessity and path of adopting the diversified management model in the media industry are explored to delve into the influence of the media diversification model and entrepreneurship on enterprise financial performance. Besides, the relevant theories such as the media diversification model and entrepreneurial spirit are expounded. Furthermore, Time Publishing & Media is taken as the representative of the media diversification model. Finally, the influence of entrepreneurship on financial performance is discussed regarding entrepreneurship in the Yangtze River Delta as the research object. The profitability, solvency, and operation ability of Time Publishing & Media are analyzed. It is found that there are problems in the profitability and operation ability of Time Publishing & Media. The solvency is good, and the risk of debt repayment is low. As a result, a diversified management model may not have a positive impact on enterprise performance. In addition, the entrepreneurial spirit of the Yangtze River Delta is studied, and the results reveal that the F values from 2017 to 2019 are about 66.24, 10.78, and 60.39, respectively, with a significance of 0.00. It implies that the stronger the entrepreneur’s ability to take risks, the better the financial performance of the enterprise, but the risk should be appropriate. Therefore, the research on the influence of the media diversification model and entrepreneurship on the financial performance of enterprises in the environment of sustainable development has guided significance for enterprises to improve their business performance and market competitiveness.